2015
DOI: 10.1080/10803548.2015.1073008
|View full text |Cite
|
Sign up to set email alerts
|

Physician exposure to violence: a study performed in Turkey

Abstract: Recently, in Turkey, there has been an increase in the number of violent acts against healthcare workers, towards doctors in particular. This study aimed to investigate the extent of violence, the causes of violence and to evaluate proposed solutions to violence. Out of 597 physicians, 86.4% indicated that they were exposed to at least one type of violence (physical, verbal, sexual) throughout their careers. Among the physicians participating in the study, 27.5% suffered physical threats and 68.6% suffered ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 8 publications
0
25
0
6
Order By: Relevance
“…Specifically, emergency medicine residents and specialists who were members of the Emergency Medicine Association of Turkey were contacted via personal e-mail, while the survey was simultaneously publicised through social networking sites to other physicians. 9 The physicians were classified according their area of expertise, as follows: (1) emergency medicine specialist, (2) emergency medicine resident, (3) specialist doctor (other than emergency medicine), (4) academic staff and (5) GP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, emergency medicine residents and specialists who were members of the Emergency Medicine Association of Turkey were contacted via personal e-mail, while the survey was simultaneously publicised through social networking sites to other physicians. 9 The physicians were classified according their area of expertise, as follows: (1) emergency medicine specialist, (2) emergency medicine resident, (3) specialist doctor (other than emergency medicine), (4) academic staff and (5) GP.…”
Section: Methodsmentioning
confidence: 99%
“…Violence against physicians is most commonly encountered in the EDs of the country. 9 Over the years, the number of patients admitted to EDs in Turkey has increased to such an extent that this number over the last 2 years is greater than the country’s entire population. This has been accompanied by an increase in incidents of violence and various other problems encountered during the provision of services in the EDs.…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmada hekimlerin %96,2'sinin çalışma hayatı boyunca en az bir kez sözel şiddete maruz kaldığı ve sözel şiddet uygulayanların hastalar, diğer hekimler ve hasta yakınları olduğu saptanmıştır. Yapılan bir çalışmada, hekimlerin %96,8'nin en az bir kez sözel şiddete maruz kaldığı belirlenmiştir (16). Türkiye'de sağlık çalışanlarına yönelik şiddeti değerlendirmek amacıyla yapılmış en kapsamlı çalışmada, çalışmaya katılan 3377 hekimin %56,9'unun son bir yılda sözel şiddete maruz kaldığı bulunmuştur (9).…”
Section: Discussionunclassified
“…Hekimlere yönelik fiziksel şiddeti değerlendiren çalışmalarda hekimlerin %8,4-%34,9'unun fiziksel şiddete maruz kaldığı saptanmıştır. Çalışmalarda fiziksel şiddet uygulayıcılarının çoğunluğunu ise bu çalışmada da olduğu gibi hasta ve hasta yakınlarının oluşturduğu tespit edilmiştir (16,18,19). Hekimlere en çok cinsel şiddet uygulayanların kendi meslektaşları olduğu yürütülen çalışmalar ve bu çalışmanın sonucunda belirlenmiştir (20).…”
Section: Discussionunclassified
“…problems. 6,7 Work place assaults are gradually increasing every years. Recent data indicated that more than twothirds of physicians experienced work-related assaults and >50% of physicians suffered WPV in the previous year, and nurses are the next most vulnerable group after doctors.…”
mentioning
confidence: 99%